Single Nucleotide Polymorphisms (SNPs) Detection in Kinases of Lung Tumors by Exon Capture and SOLiD Sequencing Technologies - Holland, K. (Association of Biomolecular Resource Facilities, 2012)
Next-generation sequencing (NGS) technologies are highly affordable and powerful tools for biomedical research. Methods for exon enrichment provide a means for focused study of protein-coding regions that may be involved in diseases. For this study, we combined Agilent exon capture and Applied Biosystems SOLiD sequencing technologies to determine single nucleotide polymorphisms (SNPs) specifically in the kinase genes of human lung tumors. Quantity and quality of genomic DNA from paired samples of normal and tumor lung tissue (N=5) were assessed with the Qubit® 2.0 fluorometer and Agilent 2100 Bioanalyzer. A Covaris® S2 system was utilized for shearing DNA (∼165 bp). After ligation of specific-adaptors, the kinase exome library was enriched using the Agilent SureSelect human kinome capture system utilizing 120-bp biotinylated RNA probes. Bound DNA was purified and barcoded for sample identification. Kinase captured libraries were quantified and pooled for amplification by emulsion PCR. Template beads for all 5 tumor-normal paired samples were pooled on a single slide and sequenced on the SOLiD 4 platform. Image analysis and base calling was performed with the SOLiD System Analysis Pipeline tool. Read length was 50 bp. GenomeQuest NGS analysis tools were used to map SOLID reads to the reference human genome (Build-hg19) as well as for SNPs identification. An average of ∼11 million reads was mapped per sample. Data analyses showed that 88.8% of the kinome probes are fully covered at a depth 1, whereas 95.55% of the probes had a depth of coverage greater than 10X. In addition, 72.2% of the sequence reads were either within or overlapping the target. Off-target reads (27.8%) were evenly distributed among chromosomes with no bias toward GC-rich regions. Overall, exon capture and NGS technologies are reliable and cost-effective approaches for SNPs detection and suitable for other applications in biomedical research.